Study of Trichomonas Vaginalis and Bacterial Vaginosis in Pap smear at a Tertiary Health Care Centre of Nepal - Pathak, Rakesh; Pradhan, P; Pudasaini, S; Maharjan, S; Basnyat, AS (Nepal Medical College Journal, 2020)
Cervical-vaginal infections are common problems in women of reproductive age presented with clinical features like white vaginal discharge, foul smelling odor and pruritis. Trichomonas vaginalis, Candidia and Gardnerella vaginalis are responsible for infectious vaginitis in creating anaerobic environment favoring Bacterial vaginosis caused by organisms like Gardnerella vaginalis, Chlamydia Trachomatis. Papanicolaou (Pap) smear examination is the simple, quick, painless routine screening test used for identification and detection of precancerous changes of uterine cervix as well as the cervico-vaginal infections resulting from bacterial, fungal and candida infections. The prime objective of the study was to identify the age wise distribution of cervical-vaginal infections and determine the frequency of Trichomonas vaginalis (TV) and Bacterial vaginosis (BV). A descriptive cross-sectional study was carried out in the Department of Pathology, Nepal Medical College and Teaching Hospital, Kathmandu. A total of 163 cases of TV and BV diagnosed on Pap smear were taken for the study. However, 564 Pap smears were received in the Department of Pathology for cytological evaluation during the study period. Once the smears were stained, the presence of clue cells, cannon balls and Trichomonas were observed. Out of 564 Pap smears received during the study period, 163 cases were of BV, TV and combined BV and TV. These 163 cases were included in our study. The age ranged from 20 to 65 years with majority (19.1%) of the women belonging to 35-39 years and the mean age was 38.18 ± 10.18 years. There were 97 cases (17.2%) of BV, 50 cases (8.9%) of TV and 16 cases (2.8%) of TV and BV co-infection. Bacterial vaginosis was the most predominant type of cervicovaginal infection followed by TV infection and TV and BV co-infections. Trichomonas vaginalis may create an environment favoring the development of BV. Pap screening could be the beneficial tool in early disease diagnosis and helps in preventing further complications by starting appropriate treatment.